Superior Labrum Anterior Posterior Lesions and Associated Injuries: Return to Play in Elite Athletes. Issue 4 (27th April 2015) - Beyzadeoglu, Tahsin; Circi, Esra
Background: Superior labrum anterior posterior (SLAP) lesions often cause shoulder pain, dysfunction, and instability. Professional athletes require a high level of shoulder function for competition and overhead activities. Purpose: To evaluate elite athletes who had arthroscopic surgery for common shoulder pathologies and SLAP lesions with a follow-up of more than 3 years. The associated intra-articular pathologies and return to play were documented. Study Design: Case series; Level of evidence, 4. Methods: Thirty-five shoulders in 34 elite athletes (4 women and 30 men; mean age, 25 years [range, 18-32 years]) had arthroscopic repair of SLAP lesions and accompanying Bankart or rotator cuff tears between January 2008 and November 2011. The documentation included patient symptoms, physical examination, radiological analysis with radiographs, and magnetic resonance imaging. Shoulder function was evaluated preoperatively and at follow-up using American Shoulder and Elbow Surgeons (ASES) and Kerlan Jobe Orthopaedic Clinic (KJOC) scores. The mean follow-up was 52 months. Results: Isolated SLAP lesions were seen in 17.1% of patients, SLAP lesions and partial cuff tear occurred in 25.7%, associated Bankart lesions in 37.1%, full-thickness rotator cuff tears in 8.6%, Bankart and posterior labrum lesions in 8.6%, and Bankart and full-thickness rotator cuff tears in 2.9%. Return to play was a mean 6.4 ± 1.5 months. The mean postoperative ASES and KJOC scores were 89.6 ± 4.6 and 80.9 ± 6.8, respectively, compared with preoperative scores of 64.0 ± 7.2 and 50.5 ± 10.3 ( t test, P < .01). Conclusion: The majority (88.2%) of professional athletes returned to their preinjury levels. SLAP lesions may frequently occur with Bankart lesions and rotator cuff tears. A high rate of return to sport at the same level of athletic performance can be achieved by anatomic repair and effective rehabilitation.